2021
DOI: 10.23910/1.2021.2212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen and Zinc on Growth and Yield of Maize (Zea mays L.)

Abstract: The experiment was laid out on the effect of nitrogen and zinc on growth and yield of maize (Zea mays L.) at Research Farm of the Department of Agriculture, Mata Gujri College, Fatehgarh Sahib, Punjab, India during kharif (July to October) season of 2017. The experiment was laid out in randomized block design three replication with eight treatments. The soil of the experimental field was Gangetic alluvial having clay loam texture with pH 7.5. It was moderately fertile, with available nitrogen (285.24 kg ha-1),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…En la Tabla 4 se presenta detalladamente los resultados del análisis del beneficio económico neto de la fertilización complementaria con Zn y Mo. Durante la temporada 2020, la fertilización complementaria con Zn y Mo alcanzó el mayor beneficio económico total del maíz y neto de la Singh et al (2021), alcanzaron mayores retornos económicos cuando la fertilización nitrogenada del maíz fue complementada con aplicaciones foliares de Zn. El mayor rendimiento, eficiencia agronómica de nitrógeno y beneficios económicos alcanzados con la fertilización edáfica complementada con nutrición foliar de Zn y Mo, en relación a la fertilización edáfica convencional, pueden relacionarse con las funciones fisiológicas que desempeña en Zn en especies C4 como el maíz, y el rol del Mo en el metabolismo del nitrógeno.…”
Section: Manejo Específico Del Experimentounclassified
“…En la Tabla 4 se presenta detalladamente los resultados del análisis del beneficio económico neto de la fertilización complementaria con Zn y Mo. Durante la temporada 2020, la fertilización complementaria con Zn y Mo alcanzó el mayor beneficio económico total del maíz y neto de la Singh et al (2021), alcanzaron mayores retornos económicos cuando la fertilización nitrogenada del maíz fue complementada con aplicaciones foliares de Zn. El mayor rendimiento, eficiencia agronómica de nitrógeno y beneficios económicos alcanzados con la fertilización edáfica complementada con nutrición foliar de Zn y Mo, en relación a la fertilización edáfica convencional, pueden relacionarse con las funciones fisiológicas que desempeña en Zn en especies C4 como el maíz, y el rol del Mo en el metabolismo del nitrógeno.…”
Section: Manejo Específico Del Experimentounclassified
“…Singh et al [25] studied the effect of nitrogen and zinc on growth and yield of maize and concluded that higher grain yields (66 q ha -1…”
Section: Yield Of Maizementioning
confidence: 99%
“…Dhananjaya and Basavaraj (2002) [10,11] documented that application of sulphur at 45 kg ha -1 increased the plant height compared to no application. Ram et al, (2003) [38,39,51] registered significant increase in plant height with application of sulphur at 60 kg ha. Maurya et al, (2005) [25] observed a significant increase in growth parameters such as height of the plant, no.…”
Section: Introductionmentioning
confidence: 99%
“…Rahul (1975) [37] concluded that application of sulphur at 90 kg ha -1 gave maximum yield in maize compared to control. Singh et al, (1987) [8,13,14,18,20,25,32,39,43,48,51,53] registered a significant increase in maize yield with application of sulphur at 22.4 kg ha -1 significantly increased the maize yield of maize up to 43.4% over control. Leary and Rehm (1990) [21] reported that sulphur application at 10 kg ha -1 gave higher yield than lower and higher levels from his study.…”
Section: Introductionmentioning
confidence: 99%